2019
DOI: 10.1136/bmjopen-2019-031607
|View full text |Cite
|
Sign up to set email alerts
|

The proximal hamstring avulsion clinical trial (PHACT)—a randomised controlled non-inferiority trial of operative versus non-operative treatment of proximal hamstrings avulsions: study protocol

Abstract: IntroductionThe treatment of proximal hamstring avulsions is controversial. While several trials have investigated the outcome for patients treated surgically, there is today no prospective trial comparing operative treatment with non-operative treatment. This protocol describes the design for the proximal hamstring avulsion clinical trial (PHACT)—the first randomised controlled trial of operative versus non-operative treatment for proximal hamstring avulsions.Methods and analysisPHACT is a multicentre randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…Previous studies have revealed noticeable ceiling effects in some non–injury-specific scores, leading to a possible overestimation and overly positive display of the results. 2 , 21 , 30 Thus, only a weak correlation between the hamstring injury–specific PHAT score and the LEFS, customized LEFS, Marx, and customized Marx scores was found, indicating that the PHAT score is perhaps the more accurate test score 2 , 3 , 5 7 and enhancing our findings.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Previous studies have revealed noticeable ceiling effects in some non–injury-specific scores, leading to a possible overestimation and overly positive display of the results. 2 , 21 , 30 Thus, only a weak correlation between the hamstring injury–specific PHAT score and the LEFS, customized LEFS, Marx, and customized Marx scores was found, indicating that the PHAT score is perhaps the more accurate test score 2 , 3 , 5 7 and enhancing our findings.…”
Section: Discussionsupporting
confidence: 54%
“… 12 , 17 , 24 Regarding the retraction of the tendon on MRI, the decision for a surgical approach was made based on a previously proposed stump retraction benchmark of 2 cm by the Wood classification. 9 , 11 , 12 , 16 , 21 , 33 Patients with a tendon retraction of less than the named benchmark (Wood type 4) were informed and counseled for nonoperative treatment; they received surgical treatment only in cases of severe symptoms (eg, sciatic nerve irritations, large hematoma) or on their explicit wish. Cases with a tendon retraction of more than 2 cm (Wood type 5) were advised to undergo surgical refixation of the tendon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first such trial of proximal hamstring avulsion injuries is currently recruiting patients to compare operative with nonoperative treatment. 21 It will be interesting to see what impact the results will have on current practice. Another option for collecting data on less common pathologies is using data registries.…”
Section: Albany Australiamentioning
confidence: 99%
“…With new standardised scoring systems such as the SHORE and PHAT tools being created, we hope to see higher level research on the best treatment for HSIs. One multicentre randomised controlled trial is currently recruiting patients to operative and non-operative treatment arms for proximal avulsion injuries 73. This will potentially improve our understanding on when to offer surgical repair along with the PHAROS, which is gathering prospective data on hamstring repair outcomes internationally.…”
Section: Discussionmentioning
confidence: 99%